Objectivity and Independence of Internal Audit (Global Journal of Management and Business Research, 2023)
Abstract- An internal audit is an important tool for companies to ensure their operations run smoothly and efficiently It is also an important way to ensure that the company s policies and procedures are being followed Internal audit processes should be objective and independent We will explore the concept of objectivity and independence of internal audit and how this affects the quality of the audit conducted by auditors It will be discussed how companies can use internal audit findings to identify areas of improvement in their operations and how they can ensure that their internal auditors remain objective and independent while performing their duties The main aim of this research is to examine the findings on how internal auditors can sustain objectivity and independence in order to provide an efficient service The paper will explore the various ways in which internal auditors can remain independent from management interference and other external influences Additionally this research paper will discuss how technology can help improve the objectivity and independence of internal audits Finally
Keywords: objectivity and independence; internal audit and credibility; reliability; assurance; and principles